PENGARUH HIGH INTENSITY INTERVAL TRAINING TERHADAP DAYA TAHAN KARDIOVASKULER, KECEPATAN DAN KELINCAHAN PADA USIA 13-15 TAHUN - Wibowo, Satria Puji Kurniawan (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
Exercise is a systematic and programmed process which carried out repeatedly with gradual loads for specific purposes such as increased agility, speed and cardiovascular endurance. HIIT is an exercise that uses high intensity with a training load above the anaerobic threshold in a short time with a resting time of 1: 2 (30 seconds: 60 seconds). The purpose of this study was to analyze the influence of the training methods of High Intensity Interval Training (HIIT) on agility, speed, and cardiovascular endurance. The type of research is quantitative with quasi experimental method using matching-only design and data analysis using t-test. This study was conducted at 20 students of the basketball team of Mawar Sharon Junior High School. The data was collected by pre-test and post-test of agility test using a squat thrust test, speed test using a 30 m run test and cardiovascular endurance test using Multistage Fitness Test (MFT). The results found that there was a significant increase in agility, speed, and cardiovascular of 14.3%, 5.2%, and 5.3%, respectively. In conclusion, HIIT training methods sessions can be used for increasing agility, speed, and cardiovascular endurance.